Progressive Failure Modelling of Transverse Cracking in Cross-Ply Laminates with Double-Edge-Semicircular Notches - Liu, C.J.; Nijhof, A.H.J.; Ernst, L.J.; Marissen, R. (Engineering Transactions, 2002)
A local-global progressive failure finite element (FEM) model was created in combination with the maximum strain criterion on an individual layer scale to study the formation of transverse cracks in cross-ply laminates with double-edge-semicircular notches. It is assumed that the laminate is made of homogeneous orthotropic layers before the occurrence of the matrix failure. Then, the average reduced layer stiffness as a function of the applied load is separated from the reduced laminate stiffness. Additionally, a maximum strain strength criterion is applied on a very local scale of a single layer to induce the local matrix failure. The initiation, propagation and multiplication of the transverse cracks starting from the notch are predicted in this way. The influences of the laminar thickness and the notch-width aspect ratios were also studied. Furthermore, the stress distribution and redistribution caused by the initiation and propagation of the transverse cracks were calculated. In addition to the stress concentration caused by the circular notch, an extra stress concentration in the 0° layers is induced by the transverse cracks in the 90° layers. This stress redistribution will in turn initiate more local failures in the 0° layers or at the interface between the longitudinal and transverse layers. The simulated results show a good agreement with experimental observations.